Gas-switchable carbon nanotube/polymer hybrid membrane for separation of oil-in-water emulsions. Issue 63 (14th August 2017) - Abraham, Sinoj; Kumaran, Surjith Kumar; Montemagno, Carlo David
Abstract : A gas responsive hybrid membrane is fabricated by surface-grafting PDEAEMA on carbon nanotubes. Abstract : A gas responsive hybrid membrane is fabricated by surface-grafting PDEAEMA on carbon nanotubes. The reversable surface wettabilites switch from hydrophobic to hydrophilic by the introduction of carbon dioxide and nitrogen gases. These can be utilized for oil/water and oil/water emulsion separations. The switchable characteristics of the CNT/PDEAEMA membrane can effectively prevent membrane clogging.